Mothering through and in Violence: Discourses of the 'Good Mother'. (August 2021) - Maher, JaneMaree; Fitz-Gibbon, Kate; Meyer, Silke; Roberts, Steven; Pfitzner, Naomi
Domestic and family violence research recognises mothering is impacted by and implicated in abusive relationships and increasingly attends to the negative impacts of domestic and family violence on children, whether or not they are direct targets of perpetrator abuse. Contemporary research also situates the undermining of the mother/child relationship as common in abusive relationships. Bringing together data from two projects – one investigating the experiences of women with disability, and one focused on women experiencing family violence from their adolescent children – we examine a further way in which mothering is impacted by family violence. While there were distinct challenges for each group of mothers, we argue that adaptable and damaging discourses of the 'good mother' impact mothers in situations of domestic and family violence. We argue that unchallenged accounts of 'good' mothers as fully responsible for their children animate persistent discourses of mother-blame. These discourses should be understood as a gendered driver of domestic and family violence.